CROSQ : From standards development to regional quality infrastructure (CROSQ St. MichaelBB, 2013)
Presents information on CROSQ and the role it plays in promoting the CARICOM Single Market and Economy (CSME) and Regional Quality Infrastructure (RQI) viz., metrology, standards, testing, certification and accreditation.
Keywords: STANDARDS